OPTIMASI KELAJUAN PEMANASAN PADA EKSTRAKSI SILIKON DIOKSIDA (SiO2 ) DARI SEKAM PADI - , Masrur (Jurnal Biofisika, 2013)
According to Central Agency Statistics Indonesia, production rice in 2012 will reach 69.05 million ton. Seeing this, it would appear the main agricultural waste generated from rice, the rice husk. Rice husk ash has the potential to produce silica. Incineration process of rice husk was performed in a furna ce at temperature of 400oC for 2 hours and 950oC for 1 hour, with the increase rate 0.5oC/minute and 1.5oC/minute. The incineration yield then washed with Chloride acid 3% (12 mL Chloride acid 3% for 1 gram of rice husk ash) and heated using hotplate and magnetic stirrer, with a speed of 240 rpm for 2 hours at 200oC. Furthermore sample washed repeatedly using hot distilled water until free acid using litmus papers, then reheated in a furnace to produce silica. EDX results for silicon dioxide of about 99.15% (for increase rate 0.5 oC/minute) and 78.96% (for increase rate 1.5oC/minute). Characterization of the silica using FTIR spectroscopy revealed the existence of functional group (siloxane). Peaks of FT-IR spectrum showed specific peaks related to the present of SiO2 at the wave number range of 1.110 cm-1 to 467 cm-1